Literary Cultures in History : Reconstructions for South Asia. - Pollock, Sheldon (University of California Press, 2003)
A comprehensive history of the rich literary traditions of South Asia, this text contains essays which consider 15 South Asian literary traditions - including Hindi, Indian-English, Persian, Sanskrit, Tibetan and Urdu - in their full historical and cultural variety.